1986
DOI: 10.1080/00140138608967234
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carried loads on the walking patterns of men and women

Abstract: In order to determine the effect of loads worn or carried on walking mechanics, 1 1 men and 1 1 women were filmed using high speed cinematography as they performed overground walking at 1-78 m/s under five load conditions. The loads included a baseline condition in which subjects carried no added load, and additional loads of approximately 9, 17,29 and 36 kg consisting of standard military items. The latter two loads were added in the form of a framed rucksack system. Values for several variables frequently us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
1
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(131 citation statements)
references
References 11 publications
(5 reference statements)
9
119
1
2
Order By: Relevance
“…As for negative work, its magnitude also increased, primarily at the hip, and mostly near the end of swing phase. This might aid the faster swing that occurred with increasing double support time and relatively constant stride time (Birrell and Haslam, 2009;Martin and Nelson, 1986). These various changes in joint work accounted for the largely parallel changes in summed joint work and COM work with load.…”
Section: Research Articlementioning
confidence: 97%
“…As for negative work, its magnitude also increased, primarily at the hip, and mostly near the end of swing phase. This might aid the faster swing that occurred with increasing double support time and relatively constant stride time (Birrell and Haslam, 2009;Martin and Nelson, 1986). These various changes in joint work accounted for the largely parallel changes in summed joint work and COM work with load.…”
Section: Research Articlementioning
confidence: 97%
“…Limited research suggests that front load carriage plays a moderate role in slips and falls although load carriage has been clearly shown to influence biomechanics of gait such as step length 15) and trunk rotations 16) . The present study was performed to evaluate if carrying a load in front would impair temporal-spatial gait characteristics (HCV, WV, and SL) and would influence slip severity (RCOF and SD I and II), and, ultimately, predisposed to slipinduced falls.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter SL while carrying the load may be induced by the mechanism caused for slower HCV 15) . Decreased SL was indicated to lessen the likelihood of slip-induced falls because it tended to reduce the horizontal shear force in proportion to the vertical force at the shoe-floor interface resulting in smaller RCOF during heel contact [3][4][5] .…”
Section: Spatio-temporal Characteristicsmentioning
confidence: 99%
“…While numerous studies have investigated the effect of carrying loads on energy expenditure (Goldman and Inapietro 1962, Leu and Mahanty 1985, Pimental and Pandolf 1979, walking patterns (Martin 1986) and perception of exertion (Goslin and Rorke 1986), o'.ly one previous study has examined alterations in pulmonary function (Legg and Mahanty 1925). Legg and Mahanty (1985) reported that with five different load carriage systems carrying a load equal to 35% of the subject's body weight reduced FVC, FEV 1 and MVV 1 5 .…”
Section: !0mentioning
confidence: 99%